2016
DOI: 10.4250/jcu.2016.24.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel De Novo Mutation of the TAZ Gene in a Korean Patient with Barth Syndrome

Abstract: Barth syndrome (BTHS) is a rare genetic disorder characterized by various types of cardiomyopathy, neutropenia, failure to thrive, skeletal myopathy, and 3-methylglutaconic aciduria. BTHS is caused by loss-of-function mutations in the tafazzin (TAZ) gene located on chromosome Xq28, leading to cardiolipin deficiency. We report a 13-month-old boy with BTHS who had a novel de novo mutation in the TAZ gene. To the best of our knowledge, this is the first reported case of a BTHS patient with a de novo mutation in K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In the majority of cases, cardiomyopathies are inherited diseases with the description of familial forms. Nevertheless, extensive screening revealed that rare “de novo” dominant mutations can occur 32–35 . In our cohort, this mechanism of pathogenicity is especially frequent, as five families presented with de novo variants or germline mosaicism (three located in MYH7 , one in ACTC1 and one in TAFAZZIN genes) indicating that these de novo mutations were expressed at a very early stage of the fetal development.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the majority of cases, cardiomyopathies are inherited diseases with the description of familial forms. Nevertheless, extensive screening revealed that rare “de novo” dominant mutations can occur 32–35 . In our cohort, this mechanism of pathogenicity is especially frequent, as five families presented with de novo variants or germline mosaicism (three located in MYH7 , one in ACTC1 and one in TAFAZZIN genes) indicating that these de novo mutations were expressed at a very early stage of the fetal development.…”
Section: Discussionmentioning
confidence: 73%
“…Nevertheless, extensive screening revealed that rare "de novo" dominant mutations can occur. [32][33][34][35] In our cohort, this mechanism of pathogenicity is especially frequent, as five families presented with de novo variants or germline mosaicism (three located in MYH7, one in ACTC1 and one in TAFAZZIN genes)…”
Section: De Novo Pathogenic Variantsmentioning
confidence: 90%
“…It should be noted that the majority of cardiomyopathies causing de novo mutations have been reported in syndromic cases such as those caused by variants in DSP (Naxos-Carvajal syndrome [3], erythrokeratodermia-cardiomyopathy syndrome [4]), LAMP2 (Danon disease [5]), PRKAG2 (glycogen storage disease of heart [6,7]), RAF1 (Noonan syndrome [8]), TAZ (Bart syndrome [9]), RRAGC (syndromic fetal dilated cardiomyopathy [10]), and LMNA (atypical progeroid syndrome and dilated cardiomyopathy [11]). Data on de novo mutations in non-syndromic cardiomyopathies are limited and include variants in ACTC [12], MYH7 [13][14][15][16], TNNI3 [17], TNNT2 [18,19], and TPM1 [20,21].…”
Section: Introductionmentioning
confidence: 99%